2015
DOI: 10.3329/bpj.v17i2.22342
|View full text |Cite
|
Sign up to set email alerts
|

Ethnomedicinal Survey of Plants in the Southern District Noakhali, Bangladesh

Abstract: Many modern medicines used today were discovered by extracting active chemicals from plants used in traditional medicine. To identify and locate any new and potential therapeutic aaplications of commonly used medicinal plants by the folk medicinal practitioners of Noakhali, Bangladesh, we conducted a survery with a semi-structured questionnaire using the guided field-walk method. Detailed information was obtained on 143 plants belonging to 62 families. Leaves were mostly used (52%) followed by roots (30.55%) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 2 publications
0
11
0
Order By: Relevance
“…Wall. Kalomegh Herb Leaves Vertigo Increase cognitive functions [ 86 , 87 ] Justicia gendarussa Burm.f. Nilnishinda Undershrub Leaves Paralysis NRE [ 88 ] Staurogyne argentea Wall.…”
Section: Introductionmentioning
confidence: 99%
“…Wall. Kalomegh Herb Leaves Vertigo Increase cognitive functions [ 86 , 87 ] Justicia gendarussa Burm.f. Nilnishinda Undershrub Leaves Paralysis NRE [ 88 ] Staurogyne argentea Wall.…”
Section: Introductionmentioning
confidence: 99%
“…(Life plant, air plant, love plant, Canterbury bells, Cathedral bells) In the treatment of urinary bladder stones (India, Trinidad and Tobago) (Lans 2006 ; Sen et al 2008 ) Leaf extract is used to cure amoebic dysentery (North Bengal) (Mitra and Mukherjee 2010 ) Wounds, bruises, swellings and insect bite (Himalaya) (Hussain and Hore 2007 ) Diarrhea (India) (Dash and Padhy 2006 ) Antibacterial and anti-inflammatory remedy (Vietnam) (Nguyen et al 2004 ) Internally: to cure acute and chronic bronchitis, pneumonia and others respiratory tract infections, fever; externally: to treat dermatomycosis (Nigieria) (Okwu and Nnamdi 2011 ) Leaves are recommended for treatment of cough in adults and children (Kibale National Park, Uganda) (Namukobe et al 2011 ) Inflammation, dermatosis, skin problems, wound healing, arthritis, asthma, bruises, diabetes, infections, tumours and ulcers—worlwide (Quazi Majaz et al 2011a , b ) Paste from macerated leaves is used externally for muscle and joint pain (Bangaldesh) (Tumpa et al 2014 ) Preparations from leaves are used to treat digestive disorders (India) (Barukial and Sarmah 2011 ) Decoction from leaves is administered to remove kidney stones (Bangladesh) (Afroz et al 2013 ) Leaves are chewed with salt as a remedy for dissolving of gall bladder stones (Bangladesh) (Rahmatullah et al 2011 ) Herbal preparation from roots and leaves is administered to women for recovering after childbirth (West Java) (Sihotang 2011 ) Leaf paste is applied externally to treat scorpion bite (India) (Vaidyanathan et al 2013 ) Leaf juice is recommended to treat cholera, diarrhea and dysentery (Bangladesh) (Khan et al 2015 ) Leaves are used to treat urinary problems, incl. kidney and gall bladder stones (Bangladesh) (Bhowmik et al 2014 ) Raw laves are chewed with sugar to treat dysentery and diarrhea; leaf juice is recommended to cure jaundice; leaf paste is used externally to heal skin infections and pimples (Bangladesh) (Das and Choudhury 2012 ) Kalanchoe tubiflora Raym.-Hamet, syn. Bryophyllum delagoense (Eckl.…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacological studies have revealed the antibacterial, antifungal, antihypertensive, anti-oxidant, antiviral, anti-feedant, insecticidal, diuretic, and hypoglycemic properties, as well as hepatoprotective, nephroprotective, and cytotoxic effects (activities) of the plants of the leguminosae family [120][121][122]. Some Leguminosae species are used to treat polymenorrhagia, anemia, ulcers, and during pregnancy [123,124]. Moreover, they also help in the treatment of diarrhea, in overcoming the protein deficiency disease, Kwashiorkor, and can also impact on the hypercholesterolemic conditions and thyroxineinduced hyperglycemia [125].…”
Section: Rosmentioning
confidence: 99%